Adaptable ciphertext-policy attribute-based encryption - LAI, Junzuo (Institutional Knowledge at Singapore Management University, 2013)
In this paper, we introduce a new cryptographic primitive, called adaptable ciphertext-policy attribute-based encryption (CP-ABE). Adaptable CP-ABE extends the traditional CP-ABE by allowing a semi-trusted proxy to modify a ciphertext under one access policy into ciphertexts of the same plaintext under any other access policies; the proxy, however, learns nothing about the underlying plaintext. With such “adaptability” possessed by the proxy, adaptable CP-ABE has many real world applications, such as handling policy changes in CP-ABE encryption of cloud data and outsourcing of CP-ABE encryption. Specifically, we first specify a formal model of adaptable CP-ABE; then, based on the CP-ABE scheme by Waters, we propose a concrete adaptable CP-ABE scheme and further prove its security under our security model.